Developing E-Module of Patient Assessment in English for Nursing Anesthesiology using Media Canva - Novi Suryati, Ni Wayan; Kadek Maya Cyntia Dewi; Putu Rusanti; Ni Kadek Ary Susandi; I Putu Agus Endra Susanta; I Gusti Agung Galuh Wismadewi (Global Action and Education for Society, 2025)
The development of effective and efficient learning media is very important and needed in the teaching and learning process in the current era of independent learning. This study aims to develop a patient assessment e-module to help students using Canva. This study applied the Research and Development (R&D) method with the ADDIE model consisting of analysis, design, development, implementation, evaluation on the product being developed. The feasibility test of the e-module with the results of the feasibility test of 86% language experts, 85% material experts and 86% media experts with an average feasibility test of 86.3% which results are included in the very feasible category. Furthermore, the results of the product test on 84 respondents students showed that 71 respondents (85%) stated very good, 11 respondents (13%) stated good, and 2 respondents (2%) stated sufficient. Based on the results of the study, it can be stated that the e-module product developed is included in the very feasible category and received a very good response from respondents because it is considered very helpful in the learning process effectively and efficiently to understand patient assessment material.